Hydrogen production by ethanol steam reforming over M-Ni/sepiolite (M = La, Mg or Ca) catalysts. (18th June 2021) - Chen, Mingqiang; Liang, Defang; Wang, Yishuang; Wang, Chunsheng; Tang, Zhiyuan; Li, Chang; Hu, Jiaxin; Cheng, Wen; Yang, Zhonglian; Zhang, Han; Wang, Jun
Abstract: Ethanol steam reforming (ESR) is a technology of great promise for hydrogen production but designing highly efficient, green and inexpensive Ni-based catalysts for inhibiting metal sinter and carbon deposition and increasing catalyst activity and stability is still a key challenge. In this paper, the M-Ni/Sepiolite catalysts (M-Ni/SEP, M = La, Mg or Ca) were synthesized using a hydrothermal-assisted impregnation method. The results from characterizations such as N2 adsorption-desorption, XRD, H2 -TPR, XPS, HRTEM and NH3 /CO2 -TPD showed that La, Mg and Ca promoters can facilitate the dispersion and exposure of Ni 0 active sites, enhance the metal-support interaction and modify surface acid/alkaline sites. Furthermore, the results of catalyst activity tests in ESR demonstrated that the Ca–Ni/SEP catalyst exhibited the highest carbon conversion of 95% and hydrogen yield of 65%, attributed to the small mean Ni particle size, strong metal-support interaction, abundant surface Ni 0 active sites and modified surface alkaline/acid sites. According to the carbon deposition analyses, it was observed in Ca–Ni/SEP that the carbon deposition amount was evidently decreased, and the graphitic degree of coke was increased due to the increased metal site amount. Graphical abstract: Image 1 Highlights: La, Mg, and Ca-promoted Ni/SEP catalysts were successfully prepared. La, Mg, and Ca promoters enhanced the capacity of Ni/SEP to sever C–C/C–H bonds. La, Mg, and Ca promoted the resistance of Ni/SEP towards active metals sintering. Ca–Ni/SEP presented the best catalytic performance for ESR reaction. Ca promoter reduced the amount of coke but increased its degree of graphitization.